A Catalogue of Oil Palm Expressed Sequence Tags (Ests) From A Floral Cdna Library and the Analysis Of Two Mads Box Genes - Kwan, Yen Yen (2004)
Flowering is a fundamental process in plant development. The transition of flowering, the first step in flower development, is triggered by a number of environmental and endogenous signals. A variety of genes combined with external and internal cues are involved in a series of biochemical and physiological changes leading to floral induction. The commercial importance of oil palm is dependent on its fruit production. Hence, flowering plays a key role in the oil palm production as the flower is an important introductory step to fruit formation. This study was conducted to isolate sufficiently large numbers of expressed sequence tags (ESTs) from floral tissue in order to obtain gene expression information on a genome wide scale. In addition, EST also provides a valuable resource of candidate genes that can be selected for further study. A random EST approach may result in the isolation of clones representing highly repeated transcripts in the floral tissue whereas low abundance transcripts may be absent. Hence, a cold plaque screening technique was employed in this study to reduce the prevalence of highly abundant transcripts as well as to facilitate isolation of low abundance transcripts. In plants, many low abundance genes encode transcription factors or proteins that are involved in signal transduction. A total of 1300 clones were isolated through cold plaque screening. Ninety-six percent of the ESTs showed homology to known sequences in the database. The remaining 4% showed no matches with anything in the database, indicating that these genes are plant-specific. Sequence analysis revealed that a large proportion of the ESTs (about 26%) encoded unknown proteins with no known functional definition in the database. The remaining ESTs were further classified into 12 groups according to their encoded putative functions. MADS-box genes are known to be important for the development of flowers and fruit. Two MADS-box cDNAS, 8-3 and 9-32, were cloned from oil palm flowers. Both 8-3 and 9-32 showed high sequence similarities to API-like MADS-box protein of rice and SEP3 from Arabidopsis respectively. Clone 8-3 was expressed predominantly in the bract, spikelet primordia and the inner two whorls of the floral primordium. The second gene, 9- 32, was expressed in flower primordia and the inner three whorls of the floral primordium. The gene expression patterns suggest that these genes have a role in regulating oil palm flower development. Oil palm is a monoecius plant that produces unisexual flowers by suppression of the development of either male or female organs in a particular whorl. Clone 9-32, which is expressed in the early stage of flowering has a different expression profile in male and female flowers The onset of 9-32 expression in the male flower is much later than in the female flower, indicating that it may be involved in sex differentiation in oil palm flowers.